ANALISIS FAKTOR PENYEBAB PENCERAIAN KARENA ORANG KE TIGA (STUDI PUTUSAN PENGADILAN AGAMA SURAKARTA NO. 777/PDT.G/2020/PA.SKA) - Halim, Abdul; Baehaqi; Syamsuddin (Fakultas Agama Islam UNISMA, 2023)
This research aims to elucidate the arguments presented by the Applicant in the Conventional/Counterclaim Defendant as the grounds for divorce due to a third party in the case decision NO. 777/PDT.G/2020/PA.SKA and how the judge's considerations in the decision of the Religious Court NO. 777/PDT.G/2020/PA.SKA as the cause of a third-party divorce.The research utilizes a descriptive qualitative method, seeking to explain problem-solving by referring to real social conditions. Data are obtained through informants with competence and relevance to the data needs. The objective of this research is to understand the implementation of participation and factors influencing participation in the study of the Divorce Law at the Religious Court in Surakarta.The results of the research indicate that the implementation of the Divorce Law has progressed as intended by the legislator, evident in the decreasing divorce rates annually. This decline is attributed to the efforts made by the Religious Court in Surakarta. Keywords: Factor Analysis, Divorce due to a third person